2002
DOI: 10.1074/jbc.m207952200
|View full text |Cite
|
Sign up to set email alerts
|

Barrier to Autointegration Factor Interacts with the Cone-Rod Homeobox and Represses Its Transactivation Function

Abstract: Crx (cone-rod homeobox) is a homeodomain transcription factor implicated in regulating the expression of photoreceptor and pineal genes. To identify proteins that interact with Crx in the retina, we carried out a yeast two-hybrid screen of a retinal cDNA library. One of the identified clones encodes Baf (barrier to autointegration factor), which was previously shown to have a role in mitosis and retroviral integration. Additional biochemical assays provided supporting evidence for a Baf-Crx interaction. The Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
82
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(84 citation statements)
references
References 68 publications
2
82
0
Order By: Relevance
“…The binding of LEM-domain proteins with BAF could similarly influence gene regulation, as BAF has been found to repress gene expression in retinal cells via binding to the homeodomain transcription factor Crx [92]. Furthermore, pull-down studies identified an emerin-binding transcription factor, Lim domain only (Lmo7), which controls the expression of emerin and many muscle specific genes [66].…”
Section: Lap-complexes Function In Gene Expression and Signalingmentioning
confidence: 99%
“…The binding of LEM-domain proteins with BAF could similarly influence gene regulation, as BAF has been found to repress gene expression in retinal cells via binding to the homeodomain transcription factor Crx [92]. Furthermore, pull-down studies identified an emerin-binding transcription factor, Lim domain only (Lmo7), which controls the expression of emerin and many muscle specific genes [66].…”
Section: Lap-complexes Function In Gene Expression and Signalingmentioning
confidence: 99%
“…We therefore hypothesized that BAF might recognize a novel motif conserved in other BAF-binding proteins that lack LEM domains, such as Crx (and related homeodomain transcription activators (23,24)), and certain histones including linker histone H1.1.…”
Section: C-terminal Domain Of Man1 Binds Transcription Regulators Gclmentioning
confidence: 99%
“…Crx is a homeodomain transcription activator; its SRV motif (residues 81-88) is located in the BAF-and DNAbinding region of Crx (residues 34 -107) (24). The E80A mutation in Crx, which alters a single residue flanking the SRV motif, disrupts Crx binding to BAF in vitro but does not disrupt Crx binding to DNA or Crx-activated gene expression (24). The SRV motif in histone H1.1 (residues 124 -131) is located within the minimal region required to bind BAF (residues 108 -215).…”
Section: C-terminal Domain Of Man1 Binds Transcription Regulators Gclmentioning
confidence: 99%
“…BANF1 was previously shown to bind two other proteins identified in the NKX3.1 interactome, emerin (EMD) and thymopoetin (TMPO) 49 . In addition, BANF1 interacts with several other homeodomain transcription factors and regulates the transcriptional activity of one of them, CRX 50 . It is thus likely that BANF1, in complex with emerin and thymopoetin, is involved in NKX3.1-mediated gene regulation.…”
Section: Resultsmentioning
confidence: 99%